2019
DOI: 10.1111/jpi.12626
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of serotonin and N‐acetylserotonin systems in the human epidermis and skin cells

Abstract: Tryptophan hydroxylase (TPH) activity was detected in cultured epidermal melanocytes and dermal fibroblasts with respective Km of 5.08 and 2.83 mM and Vmax of 80.5 and 108.0 µmol/min. Low but detectable TPH activity was also seen in cultured epidermal keratinocytes. Serotonin and/or its metabolite and precursor to melatonin, N-acetylserotonin (NAS), were identified by LC/MS in human epidermis and serum. Endogenous epidermal levels were 113.18 ± 13.34 and 43.41 ± 12.45 ng/ mg protein for serotonin (n = 8/8) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 75 publications
1
44
0
1
Order By: Relevance
“…In the skin, melatonin can regulate cutaneous pigmentation and perform photoprotective and anticancer activities [10,11]. N-acetylserotonin, a precursor to melatonin, enters the systemic circulation from different peripheral organs for transformation to melatonin [12]. Furthermore, the effects of melatonin can be mediated by its metabolites because of the rapid metabolism of melatonin at the peripheral sites [13,14].…”
Section: Mechanisms Of Melatoninmentioning
confidence: 99%
“…In the skin, melatonin can regulate cutaneous pigmentation and perform photoprotective and anticancer activities [10,11]. N-acetylserotonin, a precursor to melatonin, enters the systemic circulation from different peripheral organs for transformation to melatonin [12]. Furthermore, the effects of melatonin can be mediated by its metabolites because of the rapid metabolism of melatonin at the peripheral sites [13,14].…”
Section: Mechanisms Of Melatoninmentioning
confidence: 99%
“…The skin has its own serotonergic system. [211][212][213] Thus, targeting components of the serotonergic system has a high potential for the treatment of different inflammatory skin diseases [214][215][216] and could promote wound healing [217] and hair pigmentation, [218,219] as several studies indicate.…”
Section: Comp Ounds Targ E Ting the S Erotonerg I C And Mel Atoninementioning
confidence: 99%
“…Melatonin is a hormone product of the pineal gland that regulates the circadian rhythm. It has been observed that melatonin can be produced by epidermal and hair follicle keratinocytes ( Kleszczynski and Fischer, 2012 ; Slominski et al, 2020 , 2008 ). Melatonin has ROS scavenging properties it promotes antioxidant and DNA repair mechanisms, inducing immune modulation and antitumor properties ( Slominski et al, 2018a ).…”
Section: Amt/t For the Antiaging Use Of Mitochondriamentioning
confidence: 99%
“…This improves the mitochondrial membrane potential by inhibiting the activation of the permeability pore, stimulating the activity of uncoupling proteins (UCPs), and inducing an increase in ATP production ( Slominski et al, 2018a ). Melatonin and its derivatives N1-acetyl-N2 -formyl-5-methoxykynurenine (AFMK) and N-acetyl serotonin (NAS) are expressed in the human skin and have shown antioxidant and antiapoptotic activity ( Skobowiat et al, 2018 ; Slominski et al, 2020 ). The secretion of melatonin by the pineal gland declines with age ( Hardeland, 2012 ) and possibly affects the presence and production of melatonin in the skin.…”
Section: Amt/t For the Antiaging Use Of Mitochondriamentioning
confidence: 99%